Divided sovereignties : race, nationhood, and citizenship in nineteenth-century America - Zuck, Rochelle Raineri (The University of Georgia Press, 2016)
"In 18th- and 19th-century debates about the constructions of American nationhood and national citizenship, the frequently invoked concept of divided sovereignty signified the division of power between state and federal authorities and/or the possibility of one nation residing within the geopolitical boundaries of another. Political and social realities of the 19th century (immigration, slavery, westward expansion, indigenous treaties, financial panics, etc.) amplified anxieties about threats to national/state sovereignty. Rochelle Zuck argues that, in the decades between the ratification of the Constitution and the publication of Sutton Griggs's novel Imperium in Imperio in 1899, four racial and ethnic populations were most often referred to as nations within the nation: African Americans, Cherokees, Irish Americans, and Chinese Americans. Writers and orators from these groups engaged the concept of divided sovereignty to assert individual, communal, and national sovereignty (not just ethnic or racial identity), to gain political traction, and to complicate existing formations of nationhood and citizenship. Their stories intersected with issues that dominated 19th-century public argument and contributed to the Civil War. In five chapters focused on these groups, Zuck reveals how constructions of sovereignty shed light on a host of concerns including regional and sectional tensions; territorial expansion and jurisdiction; economic uncertainty; racial, ethnic, and religious differences; international relations; immigration; and arguments about personhood, citizenship, and nationhood"--Provided by publisher